“Cerebellar Challenge” for Adolescents at Risk of School Failure: Evaluation of a School-Based “Whole Person” Intervention - Blouchou, Panagiota; Nicolson, Roderick I. (Frontiers in Education, 2020)
Forty adolescents at risk of school failure, including 18 with a diagnosis of dyslexia, were assessed on measures of physical, cognitive and affective wellbeing. Overall both groups of participants showed marked signs of anxiety together with at risk performance on a range of cognitive and physical measures, with the dyslexic participants significantly more adversely affected on almost all measures. Half of the participants then undertook an 8 week internet-based ‘cerebellar challenge’ programme within their school environment, with the remainder having equivalent time in the existing ‘School Support as Usual’ (SSAU) activities. Compared with their initial performance, and with the SSAU group, the intervention group showed significant improvement on measures of motor performance, declarative learning, procedural learning, and mental health, both for those with dyslexia and those without. The findings are interpreted in terms of increased self-efficacy and improvements in cerebellar and hippocampal function. Given its scaleability, the intervention may prove valuable for many adolescents at risk of school failure.